2007
DOI: 10.1142/s1088424607000473
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent porphyrin-functionalized single-walled carbon nanotubes: solubilization and spectral behaviors

Abstract: We describe the solubilization/dispersion of as-produced and purified single-walled carbon nanotubes (raw-SWNTs and p-SWNTs) with protoporphyrin IX derivatives and tetraphenylporphyrin iron(III) chloride, the spectral behavior of the octaalkylporphyrins-solubilized shortened-SWNTs (s-SWNTs), and the electrochemistry of a p-SWNTs/FePP cast film on a glassy carbon electrode. Transmission electron and atomic force microscopies, as well as UV-visible-near IR spectroscopy, revealed that the protoporphyrin IX deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…On adsorption of 2 or 1 onto SWCNTs to form 3 or 4, there was no change in the Q-band maxima of the Pc, however, an enhancement in the B-band intensity due to absorption of SWCNTs was observed. Reports have shown that when Pcs or porphyrins are adsorbed onto carbon nanotubes (CNTs), there is no shift in the absorption bands of the former [46,47]. Similar lack of spectral change has been reported on adsorbing porphyrins onto SWCNTs via p-p interactions [46].…”
Section: Characterization Of Complexesmentioning
confidence: 55%
“…On adsorption of 2 or 1 onto SWCNTs to form 3 or 4, there was no change in the Q-band maxima of the Pc, however, an enhancement in the B-band intensity due to absorption of SWCNTs was observed. Reports have shown that when Pcs or porphyrins are adsorbed onto carbon nanotubes (CNTs), there is no shift in the absorption bands of the former [46,47]. Similar lack of spectral change has been reported on adsorbing porphyrins onto SWCNTs via p-p interactions [46].…”
Section: Characterization Of Complexesmentioning
confidence: 55%
“…G ⁄ is the non-dispersive phonon mode, G is the tangential vibrational mode (sp 2 ) and D is the breathing mode; disorder band (sp 3 ). CNTs, there is no shift in the absorption bands of the former [33,34], only broadening of the peaks is observed. Broadening of the spectra is observed in this work on adsorption of complex 4…”
Section: Uv-vis Spectramentioning
confidence: 89%
“…We tested a series of porphyrin derivatives and revealed that a wide range of porphyrin derivatives including 21 and 22 (Table III) can also act as effective dispersants for SWNTs. 104 The finding lead the theoretical as well as experimental attempts to understand the interaction between porphyrin and CNTs. [105][106][107] The combination of porphyrin and CNTs has attracted extensive interest due to their unique photophysical, 81,108,109 electrochemical, [110][111][112] electronic, 108,[113][114][115] and optical 116,117 properties.…”
Section: Dissolution Using Polycyclic Aromatic Compoundsmentioning
confidence: 99%